SOME CALCULATED RESULTS OF CURRENT IN THE GULF OF TONKIN BY USING NONLINEAR THREE DIMENSIONAL (3D) MODEL - Chung, Tran Van; Long, Bui Hong (Vietnam Journal of Marine Science and Technology, 2015)
Among marine investigation and study activities, the studies and calculation of dynamic system are very necessary and important, especially in the Gulf of Tonkin (Vietnam), where many economic and social activities are happening and where is affected not only by the fresh water from Red river but also by the western currents in the South China Sea through the gulf mouth and Quynh Chau Strait (between Leizhou Peninsula and Hainan Island). Up to now, the results of study, calculation and simulation of the currents in the Gulf of Tonkin with consideration on these factors and climate change effects leading to the change of occurring time, wind intensity, wind season length are very different compared to the previous results and they are still very limited and unsystematic. In this paper we tried to solve the three-dimensional (3D) nonlinear model of currents during northeast and southwest monsoons in this region using finite element method (FEM). The calculation results showed the main characteristics, the spatial and depth variation of intensity and direction of the current fields during typical monsoons in the Gulf of Tonkin. The calculation results showed that: Quynh Chau Strait plays an important role in water exchange between the Gulf of Tonkin and the South China Sea; The wind currents play an important role inside the Gulf of Tonkin and the density currents (thermo-haline, regular currents) play an important role inside and outside the main mouth of the gulf; Strong regular currents are existing (in the whole year with two wind seasons), flowing from north to south through the gulf mouth (this has been approved by some previous study results) in which the density currents play the main role; Cyclones have been formed in northeast monsoon and anticyclones have been formed in southwest monsoon in the gulf.